2021
DOI: 10.3390/cells10020304
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Metabolic Networks of Tumor Cells and Cancer-Associated Fibroblasts

Abstract: Metabolism is considered to be the core of all cellular activity. Thus, extensive studies of metabolic processes are ongoing in various fields of biology, including cancer research. Cancer cells are known to adapt their metabolism to sustain high proliferation rates and survive in unfavorable environments with low oxygen and nutrient concentrations. Hence, targeting cancer cell metabolism is a promising therapeutic strategy in cancer research. However, cancers consist not only of genetically altered tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 146 publications
0
16
0
Order By: Relevance
“…Many reviews have substantially described the interaction of CAFs and cancer cells 14 - 16 . However, recent evidence supports the critical role of CAFs as regulators of important metabolic processes in cancer 17 - 20 . These metabolism-related effects may be specific to fibroblasts in the TME and may be an adaptive mechanism to meet the metabolic demands of the rapidly proliferating tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews have substantially described the interaction of CAFs and cancer cells 14 - 16 . However, recent evidence supports the critical role of CAFs as regulators of important metabolic processes in cancer 17 - 20 . These metabolism-related effects may be specific to fibroblasts in the TME and may be an adaptive mechanism to meet the metabolic demands of the rapidly proliferating tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of the tumor metabolic reprogramming is not fully understood, as there are experimental limitations for the metabolomics studies, in that, although they are able to provide insights into the cellular metabolic status of cells, there is still a lack of information regarding the cause or effect of metabolite changes and in silico models. Integrating multi-omics data may provide a broader picture, thus enabling the identification of the regulatory mechanisms underlying in the pathophysiology of complex diseases, such as cancer [ 194 ]. The TME constitutes a complex adaptive ecological system, and due to the difficulty in modeling the interactions between multiple cell types modeling, the TME remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue was manually crumbled into small pieces and then incubated with collagenase 0.35% for 45 min at 37 • C, centrifuged, resuspended, and grown in OptiMEM (Life Technologies, Invitrogen, Milan, Italy) medium containing 10% FBS and antibiotics. All the experiments were performed at low cell culture passages (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Cell types and melanoma patient characteristics have been reported in Supplementary Table S1.…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%
“…However, recent studies have shown that stromal cells surrounding the cancer nest play a major role in progression and invasion [ 7 ]. Activated fibroblast, called cancer-associated fibroblast (CAF), is a recurrent cell type present in the tumor microenvironment [ 8 , 9 ]. This type of fibroblast demonstrated a distinct phenotype compared to its “normal” counterpart [ 10 ].…”
Section: Introductionmentioning
confidence: 99%